2005
DOI: 10.1037/0278-7393.31.3.412
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Information in Spatial Serial Memory: Path Characteristics Affect Recall Performance.

Abstract: This study examined the role of stimulus characteristics in a visuospatial order reconstruction task in which participants were required to recall the order of sequences of spatial locations. The complexity of the to-be-remembered sequences, as measured by path crossing, path length, and angles, was found to affect serial memory, in terms of both recall accuracy and response times. The results demonstrate that not all sequences are remembered equally and that spatial characteristics of the sequences constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
110
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(132 citation statements)
references
References 71 publications
(103 reference statements)
13
110
2
5
Order By: Relevance
“…Experiment 2 replicated previous studies in showing that spatial complexity impairs memory for spatial locations (see, e.g., Parmentier et al, 2005). The results are also clear in showing that spatial complexity had no effect on the recall of letters.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Experiment 2 replicated previous studies in showing that spatial complexity impairs memory for spatial locations (see, e.g., Parmentier et al, 2005). The results are also clear in showing that spatial complexity had no effect on the recall of letters.…”
Section: Discussionsupporting
confidence: 80%
“…Spatial complexity was defined as the total length of, as well as the number of crossings between, the paths connecting successive dot locations. Both the number of crossings (see, e.g., Parmentier & Andrés, 2006;Parmentier et al, 2005) and path length (see, e.g., Guérard, Tremblay, & Saint-Aubin, 2009b;Parmentier et al, 2005) have been shown to substantially decrease order memory for spatial locations. In the two-feature group, participants tried to retain both the letters and their locations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Displays with smaller stimuli separated by a larger distance increased the time for moving between the stimuli at recall but had no effect on memory accuracy. Parmentier, Elford, and Maybery (2005) found that memory for serial order of spatial locations declines with increasing length of the path connecting subsequent locations, as well as with increasing path complexity (e.g., number of path crossings). In a review of the relevant literature, Parmentier (2011) came to the conclusion that these effects of path characteristics are more likely to arise from difficulties during encoding rather than from delays imposed during maintenance.…”
Section: Decaymentioning
confidence: 98%
“…Moreover, with such a small number of dots, it is possible that participants may have formed dot patterns that could have altered the way in which the stimuli were recalled (e.g., Parmentier, Elford, & Maybery, 2005), hence reducing the sensitivity of the spatial task to distraction. The fact that the verbal and spatial tasks yielded different contexts in which the auditory deviation took place may be responsible, at least in part, for the domain-specific deviation effects reported.…”
Section: Implications For the Understanding Of Auditory Attentional Cmentioning
confidence: 99%